Historical allotment gardens in Wrocław - the need to protection = Historyczne ogrody działkowe we Wrocławiu - potrzeba ochrony - Kononowicz, Wanda; Gryniewicz-Balińska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Since about the mid-nineteenth century, together with the changing socio-economic situation, different types of allotments appeared in Wrocław. Initially, they were rented gardens, gardens for the poor or for factory workers. At the beginning of the twentieth century, school gardens and the so called Schreber gardens with a large common square were set up as part of Dr. Schreber`s educational health program. In 1914-1918, "war" vegetable gardens were commonly cultivated.
Keywords: zieleń miejska; ogrody działkowe; ochrona dziedzictwa kulturowego; Wrocław; 20 w.; urban greenery; allotments; protection of cultural heritage